Contra las interpretaciones simplistas de los resultados de los experimentos realizados en el aula - Lucas, A.M.; García-Rodeja, I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper is about the importance of the students' interpretation of experiments made in the school. Examples are given of the students' interpretations of specific activities, and possibles classroom strategies bases on these interpretations are suggested.